Analysis of Diazofluorene DNA Binding and Damaging Activity: DNA Cleavage by a Synthetic Monomeric Diazofluorene1. (9th July 2014) - Woo, Christina M.; Ranjan, Nihar; Arya, Dev P.; Herzon, Seth B.
Abstract The lomaiviticins and kinamycins are complex DNA damaging natural products that contain a diazofluorene functional group. Herein, we elucidate the influence of skeleton structure, ring and chain isomerization, D‐ring oxidation state, and naphthoquinone substitution on DNA binding and damaging activity. We show that the electrophilicity of the diazofluorene appears to be a significant determinant of DNA damaging activity. These studies identify the monomeric diazofluorene 11 as a potent DNA cleavage agent in tissue culture. The simpler structure of 11 relative to the natural products establishes it as a useful lead for translational studies.